Psychosocial consequences on relatives of femicide victims in Mexico - Bernáldez Jaimes, Germán Benito; Rodriguez Aguilar, Brenda (Acta Universitaria, 2023)
Femicide is the maximum form of violence against women, its consequences have psychological and social repercussions, extending to indirect victims. For this reason, this study aims to identify the psychosocial consequences that develop within a family when experiencing such an event, through an exploratory and qualitative analysis of the elements of quality of life, using an in-depth interview. As a result, psychosocial consequences such as alterations in self-perception and ideas of persecution, questioning of gender roles that cause female emancipation, tensions in family and social relationships, and loss of meaning were found. Results point at the possibility of structuring a life project that allows relatives of femicide victims to manage their coping skills in such a way that it influences on their state of mind and eventually on the development of comprehensive measures to reach secondary victims.